Stress-Softening Formulae of Polymer Bearings - M. H. B. M. Shariff; Anoop Sivasankaran; Zanin Kavazović (Advances in Materials Science and Engineering)
The motivation for this work was the absence of closed form solutions that can reasonably describe the axial deformation behaviour of stress-softening polymer bearings. In this paper, new closed form solutions that exhibit Mullins phenomenon are developed. We show that the apparent Young modulus depends on the shape factor and the minimal infinitesimal strain. We furthermore found that, in a nonlinear deformation, the shape factor plays an important role in stress softening. The solutions are design friendly and are consistent with expected results.